The Impact of the British Empire on its Former Colonies1707-1986 - Baali, Nabila (My University, 2017)
The British Empire was the greatest power through history and has been a turning point in the world history, too. Britain had massive impacts in many countries and Australia is one of them. This dissertation, thus, aims to analyze the effects and the expansion of the British Empire in the 19th century. This expansion raised many debates and spilled much ink. Therefore, I will shed light throughout this research on the extent of this empire to control and exercise its influence on the state of Australia. Light will mainly be shedon several areas including political, military, economic, social and cultural aspects of Australia. Furthermore, this study will spotlight on providing a historical background about the British Empire, its objectives, legitimacy and control. Also, it aims to provide a literary overview of how Australia was discovered and how Britain made it under its control. Moreover, this dissertation aims to analyze how the Australians were able to liberate themselves from the restrictions of colonialism and gain independence. Finally, this dissertation aims at focusing on the aftermath of the British and Australian relationship.
Case study Australia
Keywords: British Empir; Australia; Expansion; Colonialism; Independence; Impact